2006
DOI: 10.1562/2006-02-23-ra-811
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Warfarin Influences the Acid‐Base Equilibrium of H242 in Sudlow Site I of Human Serum Albumin

Abstract: Sudlow Site I of human serum albumin (HSA) is located in subdomain IIA of the protein and serves as a binding cavity for a variety of ligands. In this study, the binding of warfarin (W) is examined using computational techniques and isothermal titration calorimetry (ITC). The structure of the docked warfarin anion (W-) to Site I is similar to that revealed by X-ray crystallography, with a calculated binding constant of 5.8 x 10(5) M(-1). ITC experiments (pH 7.13 and I = 0.1) carried out in three different buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…Regarding ITC literature data for warfarin-HSA interaction, it should be pointed out the strong agreement between values obtained in phosphate and MOPS buffers both at the same ionic strength (100 mM) [16],and that derived in this work from HEPES buffer (50 mM), see Tables 1 and 2 kJ mol -1 [17]). Thus, it is concluded that the binding reaction is not coupled with gain or release of protons by HSA or warfarin [18].…”
Section: Resultssupporting
confidence: 81%
“…Regarding ITC literature data for warfarin-HSA interaction, it should be pointed out the strong agreement between values obtained in phosphate and MOPS buffers both at the same ionic strength (100 mM) [16],and that derived in this work from HEPES buffer (50 mM), see Tables 1 and 2 kJ mol -1 [17]). Thus, it is concluded that the binding reaction is not coupled with gain or release of protons by HSA or warfarin [18].…”
Section: Resultssupporting
confidence: 81%
“…All BSA samples were prepared in the pH 7.40 buffer solution. The concentrations of BSA, warfarin and ibuprofen in the spectroscopic samples were determined by UV absorbance measurements using an extinction coefficient of 43800 M −1 cm −1 at 280 nm for BSA [24][25], 12500 M −1 cm −1 at 308 nm for warfarin [26], and 172700 M −1 cm −1 at 308 nm for ibuprofen [27]. The concentrations of naringin and naringin palmitate were determined by high performance liquid chromatography (HPLC).…”
Section: Methodsmentioning
confidence: 99%
“…BSA was dissolved in 20 mM phosphate buffer of pH 7.0. The concentrations were measured spectrophotometrically (Shimadzu UVPC 2450) using their molar extinction coefficient values: ε 280 (BSA) = 43800 M -1 cm -1 [40], ε 308 (warfarin) = 12500 M -1 cm -1 [41], ε 280 (naringin) = 17400 M -1 cm -1 [42], ε 222 (ibuprofen) = 12700 M -1 cm -1 [43]. All the experiments were carried out in 20 mM phosphate buffer of pH 7.0.…”
Section: Methodsmentioning
confidence: 99%